Peningkatan Keterbukaan Informasi Desa dengan Pembaharuan Data Website dan Pembuatan Video Potensi Desa Olong Pinang - Hendra, Medi; Rivaldi, Ahmad; Syalsabila, Adelia; Martafola, Cristina; Rofi, Lintang Maula; Muhaenal; Savitri, Pitaloka Alif; Sasmitha; Hartono, Thirza Larence (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
Community service is one of the key components of the tri dharma of higher education. This article discusses the community service activities carried out as part of the 50th KKN UNMUL in Olong Pinang Village, a village located in Paser Balengkong District, Paser Regency, East Kalimantan Province. Olong Pinang Village already has an official website, but access to the site had experienced issues, making it necessary to improve its quality. Publications play an important role in introducing and promoting the potential of an area, whether in human resources or natural resources. Therefore, promoting the potential of Olong Pinang Village is necessary to increase its visibility and raise public awareness about the importance of digitalization in this era. The version upgrade and theme changes on the website aim to make the village site more attractive, easily accessible, and sustainably manageable. Additionally, publishing videos of the village’s potential through YouTube is expected to increase the village’s exposure and attract interest from outside communities, ultimately supporting local economic growth.